Fabrication challenges and perspectives on the use of carbon‐electrode dielectrophoresis in sample preparation. Issue 2 (31st October 2016) - Martinez‐Duarte, Rodrigo
Abstract : The focus of this review is to assess the current status of three‐dimensional (3D) carbon‐electrode dielectrophoresis (carbonDEP) and identify the challenges currently preventing it from its use in high‐throughput applications such as sample preparation for diagnostics. The use of 3D electrodes over more traditional planar ones is emphasised here as a way to increase the throughput of DEP devices. Glass‐like carbon electrodes are derived through the carbonisation of photoresist structures made using photolithography. These biocompatible carbon electrodes are not ideal electrical conductors but are more electrochemically stable than noble metals such as gold and platinum. They are also significantly less expensive than common electrode materials, both in terms of material cost and fabrication process. CarbonDEP has been demonstrated for the manipulation of microorganisms and biomolecules. This review is divided in three main sections: (i) carbonDEP fabrication process; (ii) applications using 3D carbonDEP; and (iii) challenges and perspectives on the use of carbonDEP for high‐throughput applications.